2018
DOI: 10.1002/adhm.201801043
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Osteogenesis of Bone Marrow‐Derived Mesenchymal Stem Cells by a Functionalized Silk Fibroin Hydrogel for Bone Defect Repair

Abstract: effective for bone defect treatment and bone reconstruction, these approaches are limited in their clinical application by certain constraints such as i) tissue morbidity at donor sites and the limited availability of autologous bone as well as ii) the high risk of infection and immunogenic rejection with allografts. [5][6][7][8][9] To overcome the limitations of autografting and allografting, various materials, including metals, ceramics, and polymers, have been investigated as bone scaffold biomaterials for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 56 publications
0
61
0
Order By: Relevance
“…In clinical applications, cell viability is an important parameter for evaluating the scaffold capacity to generate successful cell-biomaterial constructs. Previous studies have demonstrated that cell viability and proliferation were promoted by SF [34,35]. In this study, the SF scaffold cytotoxicity was evaluated on cultured hASCs for two weeks.…”
Section: In Vitro Biocompatibility and Osteogenic Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical applications, cell viability is an important parameter for evaluating the scaffold capacity to generate successful cell-biomaterial constructs. Previous studies have demonstrated that cell viability and proliferation were promoted by SF [34,35]. In this study, the SF scaffold cytotoxicity was evaluated on cultured hASCs for two weeks.…”
Section: In Vitro Biocompatibility and Osteogenic Differentiationmentioning
confidence: 99%
“…Previous studies have reported the osteogenic abilities of stem cells-incorporated SF to stimulate new bone formation using different scaffold designs and animal models [35,49,50]. Yan et al demonstrated that, besides mediating cell adhesion, the RGD ligands incorporated within their SF-RGD gel promoted the osteogenic differentiation of bone marrow-derived mesenchymal stem cells encapsulated within the gel matrix, leading to bone regeneration in a mouse calvarial defect model, compared with a blank SF gel [35]. Further, the functionalized SF-GO-BMP-2 composite scaffold displayed good biocompatibility and excellent proliferation effects and biological activity, thus improving bone regeneration in critical-sized bone defects and enhancing the osteogenic differentiation of BMSCs [49].…”
Section: Histological and Immunohistochemistry Analysismentioning
confidence: 99%
“…1. Silk fibroin, extracted from Bombyx mori cocoons, is a widely studied and used natural fibrous protein for diverse biomedical applications because of its advantages of abundant sources, excellent biocompatibility, great biodegradability, low toxicity and non-immunogenic features [34][35][36][37]. Although the silk materials have been employed for the drug delivery systems, most of them are merely prepared into simple morphologies or structures with less controllable capabilities due to the lack of elaborate design; this greatly limits their practical applications [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…However, the poor mechanical properties of natural protein hydrogels is one of the main drawbacks impeding their application in some cases (Silva et al, 2017;Tang et al, 2018). Recently, great efforts have been made to enhance the mechanical properties of natural protein hydrogels, and some strategies have been developed, including nanocomposite (Yuk et al, 2016;Qin et al, 2017;Wang et al, 2017Wang et al, , 2018, physical cross-linking (Toivonen et al, 2015;Feng et al, 2018;Yan et al, 2019;Zhang et al, 2019), solvent induction (Li et al, 2016;Zhang et al, 2016;Hashemnejad et al, 2017;Zhu et al, 2018), double network (Bhattacharjee et al, 2015;Luo et al, 2016;Rangel-Argote et al, 2018;Tavsanli and Okay, 2019), hybrid cross-linking (Moura et al, 2011;Epstein-Barash et al, 2012;Xu et al, 2016;Nojima and Iyoda, 2018;Yang et al, 2018), and so on.…”
Section: Introductionmentioning
confidence: 99%